Synthesis and optical characterization of color-tunable heterocyclic ligand based beryllium(II) complexes for white lighting applications. (15th June 2016) - Singh, Devender; Bhagwan, Shri; Tanwar, Vijeta; Saini, Raman Kumar
Abstract: Beryllium(II) complexes with 2-(1H-benzimidazole-2-yl)phenol (HBI) and 8-quinolinol (q) or 5-chloro-8-quinolinol (Clq) or 2-methyl-8-quinolinol (Meq) or 5.7-dimethyl-8-quinolinol (Me2 q) were synthesized and characterized. All prepared materials exhibited good thermal and electrochemical stability. The synthesized metal complexes showed bright emission on excitation with an ultraviolet light source. UV–visible absorption and photoluminescence (PL) emission spectra were recorded in order to investigate the photophysical characteristics of prepared metal complexes. The optical band gap of synthesized materials was found in the range of 3.19–3.36 eV. The beryllium(II) complexes in solid state showed emission at 479 nm for [BeHBI(q)], 481 nm for [BeHBI(Clq)], 471 nm for [BeHBI(Meq)] and 516 nm for [BeHBI(Me2 q)] materials. Temperature-dependence photoluminescence spectrum of [BeHBI(q)] complex was also studied to illustrate the effect of the substituents on the emission intensity and peak position of the spectrum. The minimal energy three dimensional molecular structures and the frontier molecular orbitals of prepared metal complexes were computed by the density functional theoretical (DFT) calculations using B3LYP correlation functional and 6-31G(d, p) basis set. The structural and the photophysical characteristics of metal complexes were tuned with introduction of electron donating group (EDG) and electron withdrawing group (EWG) on the 8-quinolinol ligand. Complexes emitting color tuned luminescence could be utilized for various field emissive devices. Graphical abstract: Photoluminescence (PL) spectra of (Be1–Be4) complexes measured in solid state at room temperature. Thermogravimetric curve (a) and differential thermal curve (b) of [BeHBI(q)] complex. Highlights: The emission spectra of metal complexes showed a red-shift or blue-shift in substituted mixed ligand based metal complexes. Prepared materials could be used with different colored electroluminophore for the development of efficient white lighting applications.